UMA ANÁLISE DO VETO À UTILIZAÇÃO DOS OBJETIVOS DE DESENVOLVIMENTO COMO DIRETRIZES DO PLANO PLURIANUAL 2020-2023 (Reflection and Critique Law Magazine, 2025)
The Pluriannual Plan is a fundamental instrument in terms of public policies, as it establishes the guidelines, objectives and goals of the federal public administration. The President of the Republic sanctioned the Union's Pluriannual Plan for the period from 2020 to 2023. However, the Chief Executive vetoed item VII of article 3 regarding the pursuit of the goals of the Sustainable Development Goals as a guideline of the PPA 2020-2023, under the allegation of violation of articles 49, item I; and 89, item VIII, both of the constitutional text. The veto was maintained by the National Congress. Therefore, the present work discussed whether the veto of the President of the Republic really has legal support in the light of the Federal Constitution and International Law. It was concluded that the grounds for the veto were wrong in the light of the constitutional text itself and International Law.